2011
DOI: 10.1093/cercor/bhr294
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Intrinsic Plasticity in Human Dentate Gyrus Granule Cells during Temporal Lobe Epilepsy

Abstract: Granule cells in the dentate gyrus are only sparsely active in vivo and survive hippocampal sclerosis (HS) during temporal lobe epilepsy better than neighboring cells. This phenomenon could be related to intrinsic properties specifically adapted to counteract excitation. We studied the mechanisms underlying the excitability of human granule cells using acute hippocampal slices obtained during epilepsy surgery. Patch-clamp recordings were combined with pharmacology, immunocytochemistry, and computer simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 68 publications
8
73
2
Order By: Relevance
“…In contrast to the last point, many studies concluded that TLE does not change DG GCs intrinsically (Mody et al, 1992a; Beck et al, 1996; Isokawa, 1996; Molnar and Nadler, 1999; Okazaki et al, 1999; Scharfman et al, 2003; Dietrich et al, 2005; Beck and Yaari, 2008). Contrary to both prior hypotheses, we found a decrease of the intrinsic excitability of GCs which was due to a reduction in input resistance (R in ); it occurred in samples of TLE patients with HS vs. mild/no HS as well as in iKA vs. control mice (Stegen et al, 2009, 2012; Young et al, 2009; Kirchheim et al, 2013). A reasonable question is: why are there so many disparate results on the same cell type (Vida, 2009)?…”
Section: Dentate Gyruscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the last point, many studies concluded that TLE does not change DG GCs intrinsically (Mody et al, 1992a; Beck et al, 1996; Isokawa, 1996; Molnar and Nadler, 1999; Okazaki et al, 1999; Scharfman et al, 2003; Dietrich et al, 2005; Beck and Yaari, 2008). Contrary to both prior hypotheses, we found a decrease of the intrinsic excitability of GCs which was due to a reduction in input resistance (R in ); it occurred in samples of TLE patients with HS vs. mild/no HS as well as in iKA vs. control mice (Stegen et al, 2009, 2012; Young et al, 2009; Kirchheim et al, 2013). A reasonable question is: why are there so many disparate results on the same cell type (Vida, 2009)?…”
Section: Dentate Gyruscontrasting
confidence: 99%
“…With rare exceptions (Isokawa and Mello, 1991; Mehranfard et al, 2014b), most studies reporting unchanged GCs were those employing TLE models without HS. In TLE patients and the iKA TLE model, the R in of DG GCs correlates with the degree of HS (Stegen et al, 2009, 2012; Young et al, 2009). Although it cannot be ruled out that some of the studies missed R in differences due to methodological procedures, such as applying minimum R in as cell selection criterion, low seal resistance sharp electrodes, or by dissociating GC somata from their dendritic conductances (Mehranfard et al, 2014b), the conservative conclusion currently is: in TLE with HS, the ion channel expression of GCs is more drastically changed than in TLE without HS.…”
Section: Dentate Gyrusmentioning
confidence: 99%
See 2 more Smart Citations
“…The shunting influence of inwardly rectifying currents on the excitability of neuronal cells, particularly, dentate granule cells, was recently demonstrated [28]. The contribution of outwardly rectifying potassium channels to somatic shunting was described in detail for the K v 3 voltage-gated potassium channel in starburst amacrine cells [29].…”
Section: Discussionmentioning
confidence: 99%